2018
DOI: 10.15252/embj.201899553
|View full text |Cite
|
Sign up to set email alerts
|

Lipid‐induced lysosomal damage after demyelination corrupts microglia protective function in lysosomal storage disorders

Abstract: Neuropathic lysosomal storage disorders ( LSD s) present with activated pro‐inflammatory microglia. However, anti‐inflammatory treatment failed to improve disease pathology. We characterise the mechanisms underlying microglia activation in Niemann–Pick disease type A ( NPA ). We establish that an NPA patient and the acid sphingomyelinase knockout ( ASM ko) mouse model show amoeboid microglia in neurodegeneration‐prone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 97 publications
4
42
0
1
Order By: Relevance
“…Microglia are responsible for the neuroinflammatory phenotype that occurs in brains of Npc1 -/mice as infiltration of peripheral macrophages could not be detected in this model (Cho, Vardi et al, 2018, Cougnoux et al, 2018. However, the contribution of microglial activation to neurodegeneration in NPC is still being discussed (Baudry et al, 2003, Gabande-Rodriguez et al, 2018, Lopez et al, 2011, Peake et al, 2011, Pressey et al, 2012. In accordance with previous reports (Baudry et al, 2003, Cougnoux et al, 2018, we detected pronounced microglial reactivity throughout cortex and hippocampus prior to neuronal loss.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Microglia are responsible for the neuroinflammatory phenotype that occurs in brains of Npc1 -/mice as infiltration of peripheral macrophages could not be detected in this model (Cho, Vardi et al, 2018, Cougnoux et al, 2018. However, the contribution of microglial activation to neurodegeneration in NPC is still being discussed (Baudry et al, 2003, Gabande-Rodriguez et al, 2018, Lopez et al, 2011, Peake et al, 2011, Pressey et al, 2012. In accordance with previous reports (Baudry et al, 2003, Cougnoux et al, 2018, we detected pronounced microglial reactivity throughout cortex and hippocampus prior to neuronal loss.…”
Section: Discussionsupporting
confidence: 92%
“…We found that in cerebellum ( Fig 3B), cortex ( Fig 3C) and the hippocampus ( Fig EV6A) of symptomatic Npc1 -/mice almost all CD68 positive cells accumulated Fluoromyelin intracellularly. Similarly, myelin accumulation was detected within microglia of symptomatic Npc-deficient mice (Gabande-Rodriguez, Perez-Canamas et al, 2018). Importantly, our proteomic analysis identified increased levels of a myelin specific protein (e.g., proteolipid protein 1, PLP1) and protein involved in microglial phagocytosis of myelin (e.g., galectin 3/LGALS3) in Npc1 -/microglia already at pre-symptomatic stages ( Fig 2C, Table EV2).…”
Section: Npc1 -/Microglia Display Enhanced Uptake But Impaired Turnovsupporting
confidence: 61%
See 2 more Smart Citations
“…Indeed, molecular evidence of microgliosis has been well established in mouse and dog models of MPS I and MPS III A, B, and C subtypes [166,182,188,190]. Inhibition of CTSB has been shown to prevent neuronal death and behavioral disorders in a patient affected by the Niemann-Pick disease type A and in a mouse model of the disease [191]. Although further studies are needed to fully elucidate the pathophysiological role of CTSs in the CNS, the above findings strongly suggest that the specific inhibition of microglial CTSs might lead to neuroprotective outcomes in MPS phenotypes characterized by activated pro-inflammatory microglia.…”
Section: Cathepsin Involvement In the Pathophysiology Of Mucopolysaccmentioning
confidence: 99%